Antiphospholipid syndrome and IgA anti-beta2-glycoprotein I antibodies: when Cinderella becomes a princess. (February 2018) - Pérez, D; Tincani, A; Serrano, M; Shoenfeld, Y; Serrano, A
IgA anti-beta2-glycoprotein I (IgA-aB2GPI) antibodies are currently not included as a laboratory criterion of antiphospholipid syndrome (APS). In the 13th International Congress on Antiphospholipid Antibodies, Galveston, TX, (USA) in 2010, these antibodies were accepted as an APS laboratory criterion in patients who had clinical manifestations of APS but were negative for "consensus" antiphospholipid antibodies (aPL) (IgG and IgM isotypes). Consequently, individuals with thrombotic events who are negative for consensus aPL may be undiagnosed for APS. The most recent publications have confirmed that IgA-aB2GPI antibodies are a risk factor for thrombotic events. In this viewpoint, we propose that IgA-aB2GPI antibodies should be included as an APS consensus criterion and that we have to help Cinderella become a princess.